LITERARY TRANSLATION AS A FORM OF INTERETHNIC LITERARY RELATIONSHIPS (ON THE EXAMPLE OF UZBEK JADID LITERATURE) - Djalilova Khurshida (Scholars Digest Publishing, 2023)
The achievements of world literature played a huge role in the formation of Uzbek Jadid literature. Literary translation occupies an important place in interliterary relations. Literary translation was a kind of impetus in the formation of a new Uzbek educational literature. It was during this period that a new galaxy of progressive poets and writers appeared. Among them, a special place is occupied by the work of Mahmudhodzhi Behbudi, Abdulla Avloni, Abdurauf Fitrat, Abdulla Kadiri, Abdulhamid Chulpan.
Keywords: literary translation; literary relations; jadidism; enlightenment; educational literature; literary process; novel; drama; poetry; genre.